Key Performance Indicator Analysis of LTE Indoor Network (Case Study : Mall Mtos Makassar) - Kalaka, Melisah; Nirwana, Hafsah; Mahjud, Ichsan (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
In today’s digital era, reliable and fast connectivity has become an important need for many people Long Term Evolution is a standard for high-speed wireless data communication for mobile phones and other data devices. This study aims to analyze the Key Performance Indicator of the LTE Indoor Network at Mall Mtos Makassar. The mall Mtos Makassar building is a shopping center, a place to watch, a place to play, etc. The Mall Mtos building has 3 large and complex floors. This measurement was carried out with 3 telecommunications operators, namely Telkomsel, Indosat Oredoo, and Xl Axiata. The parameters analyzed include Reference Signal Received Power, Reference Signal Received Quality, Signal to Interface Noise Ratio, Received Signal Strength Indicator, and Throughput Uplink Downlink. The research method used includes the walk test method with 3 floors of Mall Mtos Makassar with Idle and Dedicated mode measurements. The result of the analysis on measurement from the 1st to 3rd floors shows the signal performance between operators, thus the Telkomsel Operator shows a relatively better performance compared to the Indosat Oredoo and Xl Axiata Operators.